Eutanásia passiva, diretivas antecipadas de vontade e direito penal - Silveira, Dani Alves (2021)
The research developed deals with the legal-criminal aspects involved with passive euthanasia and the advance healthcare directive. Thus, in the first part of this research, help to death is analyzed, starting with its historical bias and progressing to its conceptual and classificatory notion, in order to provide an overview of the subject. In the sequence, the help to passive death is discussed, specifically regarding its concepts to go into the legal-criminal aspects. The second part of this research word, on the other hand, addresses the advance directives of will and the need for their study combined with help with death, given that the directives are the instrument for expressing the victim's consent. Furthermore, as there is no specific legislation on the subject in the Brazilian legal system, perhaps the solution is to use the doctrine allied to foreign law, given that in some countries there is already legislation on the subject, concluding that the lack of a national federal government law that addresses the advance directives of will should not serve as a justification for not using this institute, because in an in-depth analysis of the Constitution, advance directives of will are aligned with the autonomy and dignity of the human person.